Literacy Story Mapping: Empowering Bogoran Hamlet in Indonesia Through Among E3CHO Program - Tiasari, Luky; Rezkita, Shanta; Wahyuni, Vita Tri; Nurochman, Deyas Fito; Hapsari, Annisa; Setiawan, Dwi (ASEAN Journal of Community Engagement, 2024)
This paper outlines the implementation of Among Education, Environment, Economic, Culture, Healthy, and Outcome (Among E3CHO), a community engagement program in Bogoran Hamlet in Trirenggo Region of Bantul Regency, Yogyakarta, Indonesia. Among E3CHO initiative consists of multiple education, environment, economic, culture, and health engagement sessions aimed at generating a literacy story map, Peta Cerita Berliterasi, as an integrated outcome of community capacities. The program development followed community-based research methodologies, starting with the identification of challenges facing by the community using comprehensive questionnaires, followed by multiple community engagement programs. In the program, the health engagement session focuses on nutrition, and the economic session focused on tempeh dumpling preparation techniques. The educational environment engagement focuses on the cultivation of vegetables, medicinal herbs, flowers, and fruit plants using pots from repurposed plastic waste. Subsequent reflection and evaluation of each of the session in the programs were conducted to measure their efficacy and community satisfaction. The program led to a significant increase in knowledge of balanced nutrition, culinary arts, and cultural heritage among the community of Bogoran Hamlet. The integration of multiple aspects within one program increased the capacity of the Bogoran Hamlet community, creating a transformative literacy quality toward a sustainable positive impact on society.